Estudo microgravimétrico da formação de filmes de prata eletrodepositados - Matos, Roberto de (Universidade Federal de São Carlos, 2009)
In this thesis, a voltammetric coupled to microgravimetry investigation about the electrodeposition of silver over polycrystalline platinum in acid medium was performed. Microgravimetry is helpful to understand the effect of different preparation variables, such as, pH, temperature, ion concentration and applied potential. This, in its turn, is a consequence of the fact that the composition in not the only important characteristic of electrodeposited metal which depends on the preparation process. We choose to study silver deposition once it is, in principle, a simple one electron process. The obtained data reveal a much more complex with several cathodic and anodic processes. First, the UPD silver deposition occurs, then the bulk and also the hydrogen evolution during the cathodic sweep. During the anodic voltammetric sweep, two current density peak were observed with molar mass equal to Ag dissolution, and then we conclude that a hydrogen rich phase or an alloy Pt-Ag were formed during the process. For one of solution investigated, a third anodic process was observed which could be associated to silver oxide formation and dissolution.
Microgravimetric study of the formation of electrodeposited silver films
Keywords: Eletroquímica; Eletrodeposição; Filmes finos; Prata; Microbalança de cristal de quartzo; CIENCIAS EXATAS E DA TERRA::QUIMICA